Prospective study of power generation from natural resources using hybrid system for remote area - M. F. Yaakub; F. H. Mohd Noh; M. F. I. Mohd Zali; M. H. Harun (Institute of Advanced Engineering and Science, 2020)
Living in the 21st century, electricity has become a need in every society level. However, numbers of the remote area, especially in third world countries still facing difficulty to reach a grid-connected electricity due to various reasons. As such, this paper presents a prospective study of generating an electrical energy that is converted by utilizing natural resources from the sky. It is realized by implementing a hybrid solar-rainwater harvesting system. Combination of 12Vdc 3Watt solar cells and 3.7 Vdc 129mW pico-hydro implemented in the work has given a great yield reaching average 921 milliwatts of energy produced by the natural resources.